Analisa Kapasitas dan Kebutuhan Daya Pada Sistem Distribusi Feeder Benu-Benua - Buransa, Armin Sole; Mangalla, Lukas Kano; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2024)
The distribution system is part of the electric power system. This distribution system is useful for distributing electricity from large power sources (bulk power sources) to consumers. However, in this distribution there are often obstacles such as disturbances in the distribution network system. In general, the good and bad of the electricity distribution and distribution system is mainly in terms of the quality of the power received by consumers. This research was conducted to determine the capacity and demand for electricity used against the load in the city of Kendari and to determine the care and maintenance of the distribution system in the city of Kendari. In collecting data, a field survey was carried out at the research location, namely at the New Kendari 150 KV Substation. At the largest average load occurs in the old city line with a power of 38.734,25. While the peak load and demand factor on each line has a different amount. And the biggest voltage loss occurs in the alolama line of 9,9% and the lowest in the old city line of 3,8%. It can be concluded that on the Kemaraya Line the average load obtained is 38.839,25 with the highest load occurring at 18.00 at 6,068 while the highest demand factor occurs on the Kemaraya Line at 19.00 at 134,5. Kata kunci: Load Factor, Capacity, Power Requirements